Medan Plaza Hotel and Mall As One of The Icons of Medan City (Monumental Architecture) - Albert Tambunan; Wahyu Utami (International Journal of Architecture and Urbanism, 2018)
Medan Plaza that built in 1982 is one of the pioneers of high-rise malls and buildings that can be considered modern and became the pride of the city of Medan. Over time, more than twenty years later, more and more malls have sprung up in Medan and also building mall coupled with the hotel or apartment. The liability to build high-rise buildings is also the answer to the increasing lack of land in the city center. Besides that, high-rise buildings which interconnected with each other are answers to the needs of the times, that constitute an integrated unit of an organism, the city, which has various activities connected to each other in a system. Hotel and mall have a crucial role in meeting the needs of society. The existence of a single entity with the hotel mall gives ease in meeting the needs of shopping and sightseeing the hotel guests. Facilities at the hotel also required of the general public that with the restaurant, pool, ballroom, gym, etc. Hotel and the mall is a response to the needs of a complex society.